Cytoplasmic molecular chaperones in Pseudomonas species - Kim, Hyunhee; Moon, Seongjoon; Ham, Soojeong; Lee, Kihyun; Römling, Ute; Lee, Changhan (Journal of Microbiology, 2022)
Pseudomonas is widespread in various environmental and host niches. To promote rejuvenation, cellular protein homeostasis must be finely tuned in response to diverse stresses, such as extremely high and low temperatures, oxidative stress, and desiccation, which can result in protein homeostasis imbalance. Molecular chaperones function as key components that aid protein folding and prevent protein denaturation. Pseudomonas, an ecologically important bacterial genus, includes human and plant pathogens as well as growth-promoting symbionts and species useful for bioremediation. In this review, we focus on protein quality control systems, particularly molecular chaperones, in ecologically diverse species of Pseudomonas, including the opportunistic human pathogen Pseudomonas aeruginosa, the plant pathogen Pseudomonas syringae, the soil species Pseudomonas putida, and the psychrophilic Pseudomonas antarctica.
Keywords: Biodegradation, Environmental; Humans; Molecular Chaperones; Plants; Pseudomonas aeruginosa; Pseudomonas syringae; molecular chaperone; protein homeostasis; Pseudomonas; Pseudomonas aeruginosa; Pseudomonas antarctica; Pseudomonas putida; Pseudomonas syringae; Pseudomonas thermotolerans